2011
DOI: 10.5402/2011/465198
|View full text |Cite
|
Sign up to set email alerts
|

Meibomian Gland Dysfunction: Endocrine Aspects

Abstract: Purpose. To compare the hormone levels of patients with seborrheic meibomian gland dysfunction with controls. Procedures. This is a retrospective case-control study involving 50 patients and 50 controls. Blood workup for hormones was studied in both groups by using macroELISA (enzyme-linked immunosorbent assay). Statistical evaluation was done by using SPSS 15.0 independent samples t-test. Results. There were statistically significant differences of serum testosterone and dehydroepiandrosterone sulphate levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In contrast, PRL blood serum concentration has been shown to correlate negatively with tear quality in women on hormone replacement therapy (18). In another study, women, but not men, with seborrheic MGD revealed significantly higher PRL levels in blood serum compared to controls (45). Both studies did not include PRL concentration or other hormonal factors in the donor tears.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, PRL blood serum concentration has been shown to correlate negatively with tear quality in women on hormone replacement therapy (18). In another study, women, but not men, with seborrheic MGD revealed significantly higher PRL levels in blood serum compared to controls (45). Both studies did not include PRL concentration or other hormonal factors in the donor tears.…”
Section: Discussionmentioning
confidence: 94%
“…With regard to the meibomian gland, investigators have found that women, but not men, with seborrheic MGD have significantly elevated serum levels of prolactin [772]. The reason for this linkage is unknown.…”
Section: Effects Of Hypothalamic-pituitary Hormonesmentioning
confidence: 99%
“…These receptors are thought to be the target for autoantibodies in thyroid-associated ophthalmopathy, and, possibly through aberrant signal transduction, contribute to the reduced aqueous tear secretion and ocular surface damage in this disorder [793]. TSH levels in the serum of women, but not men, are also increased in seborrheic MGD [772]. The basis for this correlation is not known.…”
Section: Effects Of Hypothalamic-pituitary Hormonesmentioning
confidence: 99%
“… 23 , 24 Furthermore, testosterone deficiency has been shown to promote meibomian gland dysfunction especially in patients taking antiandrogen therapy. 18 , 25 These patients showed changes in the appearance of the meibomian glands as well as a reduced quality of meibum secretion. 19 Ocular surface effects of estrogens on the meibomian glands are more controversial, although it is thought that a high level of serum estradiol is a risk factor for dry eye 26 through its suppression of lipid synthesis and promotion of lipid catabolism in the meibomian glands.…”
mentioning
confidence: 99%